Class, State, and Power in the Third World : with case studies on class conflict in Latina America. - Petras, James F.; DeWitt, Peter; Havens, A. Eugene; Morley, Morris H. (New Jersey; London US; GB: Allanheld, Osmun & Publishers; Zed Press, 1980)
Trata acerca del crecimiento de la industria y negocio militar.
Keywords: AMERICA LATINA; PAISES EN DESARROLLO; CLASES SOCIALES; PODER